Flavour chemistry of palm toddy and palm juice: a review. - Olusegun, Lasekan; Abbas, Kassim Ali (Elsevier, 2010)
Systemic analytical approaches aimed at characterizing key odourants, such as Aroma Extraction Dilution Analysis (AEDA), PTR-MS, EXOM, ADA and Stable Isotope Dilution Assays (SIDA) are very useful tools for elucidating the flavour and off-flavour components in palm toddy and palm juice. On the basis of results obtained using these techniques, it was shown that 3-isobutyl-2-methoxypyrazine (earthy), acetoin (buttery), ethylhexanoate (fruity) and 2-acetyl-1-pyrroline (popcorn-like) are important odourants of palm toddy. However, the typical flavour components of palm juice were ethyl lactate, 3-hyroxy-2-pentanone, and ethylhexanoate. In addition, the off-flavour component which developed in toddy during consumption was identified.